Esperanza y curación: la trascendencia de la espiritualidad y la religiosidad en la recuperación de casos graves de SARS-CoV-2 (Research, Society and Development, 2021)
This work is based on the importance of understanding the relationship of spirituality and religiosity in the healing process of SARS-CoV-2, interchanging experiences and concepts of healthcare professionals in the process of caring. The overall goal of the study was to find in spirituality and religiosity a joint factor for recovering patients from serious cases of Sars-Cov-2. The research approach focused on the qualitative, applied type, exploratory character, field and bibliography. The study was carried out with 5 nurses who worked in the Intensive Therapy Unit for COVID-19 wing of a Reference Hospital, in a city of Interior Maracana, data collection took place from September to October of 2021, with the questionnaire recorded by audio and transcribed later. The study made it possible to observe that spiritual and religious power can help deal with serious cases, mainly in terms of mental health. Therefore, in terms of spirit, when revealed the basic needs of the human being, nurses must have full capacity to recognize and understand, identifying the needs of each patient, by communicating with him and his family.